Гормонально-імунологічні особливості ендометріозу матки у жінок з патологією щитоподібної залози та безпліддям - Постоленко, Вікторія Юріївна; Постоленко, В. Ю.; Postolenko, V. (Чорномор. нац. ун-т ім. Петра Могили, 2018)
Метою дослідження стало визначення особливостей гормонального, імунологічного та ендотеліального статусу у жінок з аденоміозом та патологією щитоподібної залози при лікуванні безпліддя. Всього було обстежено 64 жінки, які проходили підготовку до ЕКЗ у програмі ДРТ у зв'язку з безпліддям. Першу клінічну групу склали жінки з ендометріозом матки без патології щитоподібної залози – 24 (37,5%). Другу клінічну групу склали жінки з патологією щитоподібної залози та ендометріозом матки - 20 (31,25%). Контрольну групу склали жінки без ознак ендометріозу та патології щитоподібної залози – 20 (31,25%). Визначені ультразвукові особливості вузлової та дифузної форм аденоміозу, зміни у гормональному, імунному, ендотеліальному статусі при ендометріозі матки та гіпотиреозі у жінок з безпліддям. Резюме. Целью исследования стало определение особенностей гормонального, иммунологического и эндотелиального статуса у женщин с аденомиозом и патологией щитовидной железы при лечении бесплодия. Всего было обследовано 64 женщин, которые проходили подготовку к ЭКО в программе ВРТ в связи с бесплодием. Первую клиническую группу составили женщины с эндометриозом матки без патологии щитовидной железы – 24 (37,5%). Вторую клиническую группу составили женщины с патологией щитовидной железы и эндометриозом матки – 20 (31,25%). Контрольную группу составили женщины, у которых отсутствуют признаки эндометриоза и патологии щитовидной железы – 20 (31,25%). Определены ультразвуковые особенности узловой и диффузной форм аденомиоза, изменения в гормональном, иммуно, эндотелиальном статусе при эндометриозе матки и гипотиреозе у женщин с бесплодием. Abstract. The last decades have been characterized by the increasing proliferation of auxiliary reproductive technologies for the treatment of infertility. According to the literature data, the incidence of endometriosis in women with infertility varies from 30 to 60%. In addition, endometriosis, in particular adenomyosis, prevents the increase of the effectiveness of extracorporal fertilization. Thyroid gland plays an indirect role in the development of endometriosis. Deviations in the physiological secretion of thyroid hormones that act as modulators of estrogens at the cellular level contribute to the disruption of the hormone-sensitive structures in the formation of genital endometriosis. The purpose of the study was to find out the peculiarities of hormonal, immunological and endothelial status in women with adenomyosis and pathology of the thyroid gland, in particular hypothyroidism. Material and methods. To achieve the goal, we examined 64 women who were to receive in vitro fertilization extracorporeal fertilization. All women were divided into groups depending on the presence of adenomyosis and pathology of the thyroid gland. The first clinical group consisted of women with endometriosis of the uterus, which had no pathology of the thyroid gland – 24 (37.5%) patients. The second clinical group consisted of women with pathology of the thyroid gland and endometriosis of the uterus – 20 (31.25%) patients. The control group consisted of women who had no signs of endometriosis and pathology of the thyroid gland – 20 (31.25%) patients. The age of the patients varied from 25 to 38. Results and discussion. The results of ultrasound examination showed nodal adenomyosis in 23 (35.9%) patients. The dimensions of adenomyosis nodes ranged from 10 to 35 mm (on average 29±7 mm), in most cases they were intermixed, but in 12.5% there were submucosal or sub-gray areas. The results of the hormonal study demonstrated a probable reduction in FSH secretion in women with adenomyosis and hypothyroidism compared to the first group (3.5±0.6 mM/ml and 8.1±0.7 mM/ml respectively) (p <0.05). A similar trend was observed in relation to estradiol (159±24 ng /l and 101±13 ng/l). We did not detect differences in LH secretion (7.2±1.1 mM / ml and 6.9±1.3 mM/ml). Prolactin levels were slightly higher in the group with adenomyosis and pathology of the thyroid gland (18.3±3.7 ng /ml and 12.1±2.9 ng/ml). When comparing thyroid hormones, it was clear that they were deviant from the norm only in the group of women with hypothyroidism (TSH – 6.9±0.8 mMo/l; T3 – 5.3±0.4 pmol/l; T4 – 2.7±0.6 pmol / l). In the immunological study, we determined IgM increase in women with pathology of the thyroid gland (2.7 ± 0.2 g/l). The level of autoantibodies to tireopexidase and tireoglobulin was likely to increase in patients with hypothyroidism (118±21 IU /ml and 312 ± 34 IU/ml, respectively). In the study of cellular immunity, it was determined that CD3 (1.2±0.02), CD4 (0.9±0.05), CD8 (0.7±0.01) and FNP (7.9±0.8 pg/ml) decreased with hypothyroidism, and CD16 (0.8±0.04) and СD20 (0.7 ±0.03) increased. The secretion of IL-1 (5.6±0.6 pg / ml) and IL-10 (15.3 ± 1.1 pg / ml) was higher than that of women with normal thyroid status, and the level of IL-6 (7.2±0.9 pg / ml) and IL-8 (61.6±3.1 pg / ml) were low. In adenomyosis, we observed an increase in IgM content (0.9±0.02 g / L) and a decrease in IgA (0.2±0.01 g / l) in peritoneal fluid in comparison with control parameters. In the study of VEGF, the following results were obtained: in the first group VEGF levels ranged from 125.2 to 208.9 pg / ml, averaging 148.5±13.1 pg / ml. In the second group, the concentration of VEGF ranged from 158.6 pg / ml to 294.3 pg / ml and equaled 214.8±16.5 pcg, which is significantly different from the standard values of control group women (p <0.05). In the study of concentration of endothelin-1, we determined an increase in its serum content in women of the second group to 11.8±1.9 ng / ml in comparison with the control group parameters (3.4±0.8 ng /ml). Conclusions. In the context of hypothyroidism there was a decrease in the follicle stimulating function of the adenohypophysis and estrogen producing ovaries, inhibition of the cellular immunity, and activation of the humoral link, changes in the cytokine status, especially local immunity, expressed endothelial disorders in patients with adenomyosis. The determined changes were more pronounced in the diffuse form of uterine endometriosis in women with infertility.
Гормональные иммунологические особенности эндометриоза матки у женщин с патологией щитовидной железы и бесплодием
The Hormonal-Immune Abnormalities of Uterus Endometriosis in Women with Thyroid Gland Pathology And Infertility
Keywords: ендометріоз матки; гіпотиреоз; безпліддя; локальний імунітет; ендотеліальний статус; ультразвукове дослідження; інтерлейкіни; эндометриоз матки; гипотиреоз; бесплодие; локальный иммунитет; эндотелиальный статус; ультразвуковое исследование; интерлейкины; endometriosis cancer; hypothyroidism; infertility; local immunity; endothelial status; ultrasound; interleukins